Data on SSR markers and SNPs filtered from transcriptome of Parvocalanus crassirostris - Nazima Habibi; Saif Uddin; Montaha Behebehani; Mohd Wasif Khan; Nasreem Abdul Razzack; Faiz Shirshikhar (Data in Brief, 2023)
Calanoid copepod populations are being severely affected due to the effects of ocean acidification (OA) and ocean warming (OW). These marine organisms are the most abundant primary consumers contributing significantly in the marine food web. Any effect on the abundance and diversity of copepods due to climate change is likely to have serious implications on the marine ecosystem functioning. Molecular studies that play a vital role in assessing the genetic changes under the influence of environmental imbalances are completely lacking for this species. Here we report the genetic variations in three generations of copepods through transcriptome sequencing. RNA sequencing was performed on an Illumina HiSeq platform employing the 2 × 100 bp paired-end chemistry. Approximately, 10GB of data was obtained for all the samples. The raw sequences were assembled through Trinity 2.6.6 and mined for single nucleotide polymorphisms (SNPs) and simple sequence repeats (SSRs). MIcroSAtellite Identification Tool (MISA) was used for SSR detection and Primer 3 (v 3.0) was utilized to design short oligonucleotide primers (18-20 mers). A total of 15,222 SSRs were identified and 28,944 primer pairs were designed against these motifs. The transcriptome possessed 413,890 SNPs at a frequency of 2.8 per kb. The newly discovered SSRs and SNPs could act as genetic markers for future studies on genetic diversity and conservation for Parvocalanus crassirostris.